WAYS OF INTEGRATION OF TRADITIONAL CHINESE EMBROIDERY IN MODERN VISUAL DESIGN - CHENG , KAI; SKLIARENKO, N. V. (Art and Design, 2024)
Purpose of the study is to identify innovative ways to integrate elements of traditional Chinese embroidery into contemporary visual design and its significance for cultural heritage and design innovation. Methodology. The research is systematic and interdisciplinary. The research methodology is based on a combination of historical and cultural analysis and the case method. The historical and cultural background of Chinese embroidery is studied through the analysis of literature, art historical and cultural analysis. The article analyses examples of the use of embroidery in modern design fields, including fashion, graphics, industrial design and digital media, which allowed us to assess the possibilities of their innovative integration. Results. It has been found that the modern use of traditional embroidery elements in various areas of design not only enriches visual images, but also plays an important role in the dissemination of culture and the development of creative thinking. The innovative application of embroidery elements in fashion design (as a decorative element, as a digital print, as a formative element of clothing), graphic (as a means of communication) and industrial design (as a functional element), digital media (as an audio-visual and sensory experience) and interdisciplinary integration not only demonstrates a wide range of possibilities for combining tradition and modernity, but also provides designers with new sources of inspiration. Scientific novelty. The article presents a new perspective on the understanding and use of traditional Chinese artistic crafts in contemporary design. Combining the cultural and artistic values of traditional embroidery with the needs of modern visual design opens up wide opportunities for innovative applications and interdisciplinary collaborations, promoting deeper integration of traditional elements into various design fields. Practical significance. This research opens up new opportunities for using traditional culture in contemporary design to preserve national identity. It will not only stimulate the creative thinking of designers, but also increase public awareness and respect for traditional culture, and promote the prosperity and synthesis of national traditions and design innovation. By preserving national culture and developing contemporary national aesthetic concepts, it ensures that traditional artistic resources remain relevant and influential in a globalised world.